When do caregivers begin to view their child as a moral agent? Comparing moral and non-moral reactions to young children's moral transgressions. Issue 3 (3rd July 2021) - Essler, Samuel; Paulus, Markus
ABSTRACT: Caregivers' moral reactions to young children's moral transgressions are informative environmental responses for children's developing understanding of morality. One central question concerns by which age parents hold their children responsible for moral transgressions. This study indirectly investigated this question by having parents and non-parents ( N = 150) rate the appropriateness of caregivers' moral and non-moral reactions to moral transgressions of 6-month-old, 1-year-old, 2-year-old, and 4-year-old children. Transgressions and reactions were presented as short video clips in an online survey. Results indicated that moral reactions were judged as increasingly appropriate and non-moral reactions as increasingly inappropriate with age. Two years constituted a turning point, after which moral reactions were judged as more appropriate than non-moral reactions. This pattern showed to be the same for parents and non-parents. These findings highlight the growing importance of moral reactions over the first years of life and lend support to theories of intuitive parenting.